The Relation of Mother’s Knowledge, Parenting Patterns and Household Food Security Status with Stunting Case in Children Aged 6-23 Months (Regional Study of Landasan Ulin Health Center, Banjarbaru City) - Jannah, Raudhatul; Nurhamidi, Nurhamidi (Journal of Local Therapy, 2025)
Stunting is a condition of failure to thrive due to malnutrition for a long time so that children are shorter than normal children their age. Stunting is not only caused by one factor but by many factors. The prevalence of stunting at the Landasan Ulin Health Center continued to increase from 2018 (16.0%), 2019 (21.89%) and 2020 (22.26%). Objective: To determine the relationship between maternal knowledge, parenting and household food security status with the incidence of stunting in children aged 6-23 months in the working area of the Landasan Ulin Health Center, Banjarbaru City. Methods: This type of research is an observational analytic study with a Cohort Retrospective design. The population of this study was all children aged 6-23 months in the working area of ??the Landasan Ulin Health Center and a sample of 92 children using the purposive sampling technique. Results: The knowledge of the mothers of children under two years was in the less category (47.8%), the parenting pattern for the children was in the sufficient category (39.1%), the household food security status was mostly classified as food insecure (42.4%) and the children who experienced stunting were less (40.2%) . Conclusions: There is a relationship between mother’s knowledge, parenting, and household food security status with the incidence of stunting in children aged 6-23 months in the working area of ??the Landasan Ulin Health Center.